1996
DOI: 10.1101/gad.10.10.1284
|View full text |Cite
|
Sign up to set email alerts
|

Ptx1, a bicoid-related homeo box transcription factor involved in transcription of the pro-opiomelanocortin gene.

Abstract: The pituitary gland contains six distinct hormone-producing cell types that arise sequentially during organogenesis. The first cells to differentiate are those that express the pro-opiomelanocortin (POMC) gene in the anterior pituitary lobe. The other lineages, which appear later, include cells that are dependent on the POU factor Pit-1 and another POMC-expressing lineage in the intermediate pituitary lobe. Using AtT-20 cells as a model for early expression of POMC in the anterior pituitary, we have defined a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
306
1
9

Year Published

1997
1997
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 396 publications
(321 citation statements)
references
References 50 publications
5
306
1
9
Order By: Relevance
“…This suggests that in fish pitx3 has possibly subsumed the function of mammalian Pitx1/2. By trans-activating reporter assays it was shown that mouse Pitx1 can drive Lhx3 (the mouse homolog of zebrafish lim3) as well as prl and pomc expression (Lamonerie et al, 1996, Tremblay et al, 1998. Since Pitx binding sites have also been found in the zebrafish pomc promoter, and since lactotropes and corticotropes are the first differentiating AH cells of the zebrafish, one can speculate about a similar regulation of these genes by Pitx3 in teleosts (Liu et al, 2003).…”
Section: Pitx3mentioning
confidence: 99%
“…This suggests that in fish pitx3 has possibly subsumed the function of mammalian Pitx1/2. By trans-activating reporter assays it was shown that mouse Pitx1 can drive Lhx3 (the mouse homolog of zebrafish lim3) as well as prl and pomc expression (Lamonerie et al, 1996, Tremblay et al, 1998. Since Pitx binding sites have also been found in the zebrafish pomc promoter, and since lactotropes and corticotropes are the first differentiating AH cells of the zebrafish, one can speculate about a similar regulation of these genes by Pitx3 in teleosts (Liu et al, 2003).…”
Section: Pitx3mentioning
confidence: 99%
“…To approach the similar mechanism of maternal regulation in embryo development, some bicoidrelated genes are recently reported in chick [15], [17] mouse [18] and other animals, which are mostly characterized by the lys-9 of helix3 [16]. However, there is still not any bicoid-related gene reported in higher plant yet, although the polarity of embryo has been reported in higher plant (2).…”
Section: Discussionmentioning
confidence: 99%
“…To compare the homeodomain conserved region between RB24, Drosophila bicoid gene [14], [1] and other chicken and mouse bicoid-related genes [15], Block Maker software were used for analysis of highly conserved regions of proteins. The results indicates two conserved block regions in bicoid (Drosophila), and Rb24(rice), Ptx1(chicken), Gsc(mouse), Otx1(mouse) bicoid-related genes, which just cover putative helix1 and helix3 region in bicoid homeodomain (Fig 1A).…”
Section: Cloning Of Rice Bicoid Related Cdna Sequencementioning
confidence: 99%
“…Ptx1 is closely related to the mammalian Otx gene, which is expressed in the rostral brain during the process of development (37,38), and Otx2 is a fundamental factor related to forebrain and midbrain development in mice (39). Ptx1 mRNA is strongly expressed in adult corticotroph cells, which secrete POMC, whereas its expression in Rathke's pouch has also been detected using the in situ hybridization technique (17). Thus, there remains a possibility that Ptx1 is expressed in pituitary cells other than corticotrophs, so that its activities need further investigation, including the relationship with other transcription factors related to pituitary cells.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the activation of Pit-1 by Prop-1 may be triggered through the disappearance of Rpx/Hesx-1. On the other hand, a novel transcription factor pituitary homeo box 1 (Ptx1) has been initially introduced as a factor toward the expression of proopiomelanocortin (POMC) (17). But, in the studies on rat pituitary glands and cultured cells, Ptx1 has been expressed not only in the POMC secreting cells but also in the other hormone secreting cells of the anterior lobe as well as in the cell lines of various different hormone productions (16).…”
mentioning
confidence: 99%